Biochemical abnormality in the Brown Swiss breed cows affected with ketosis in the perinatal period - Efimov, V.; Efimov, Valentyn; Efimov, V. G.; Yefimov, V.; Yefimov, Valentyn; Yefimov, V. G.; Yefimov, V. H.; Iefimov, V. G.; Jefimov, V. H.; Jefimov, V. G.; Jefimov, V.; Jefimov, Valentyn; et al. (Дніпровський ДАЕУ, 2023)
Ketosis is widespread disturbance among dairy cows, causing signifiant economic losses and requiring further study of its pathogenesis. This particularly applies to less traditional dairy breeds, including the Brown Swiss. The aim of the study was to investigate the biochemical indicators in the Brown Swiss breed cows of different age at a stage with prevalent ketosis. The research was conducted on a dairy cow herd with a ketosis level exceeding 30%. Blood samples were collected from primiparous cows and cows in their 2nd-3rd lactation 5-7 days before calving (group BC), post calving 2-3 days (group 2-3 PC), and 7-10 days (group 7-10 PC). Biochemical indicators of blood serum aimed at determining the level of lipomobilization, ketone bodies, and liver function were determined using an automatic biochemical analyzer. In the group of primiparous cows 2-3 PC, there was an increase in the content of beta-hydroxybutyrate by 1.83 times, and ketonemia was observed in 40% of cows. The postpartum period in primiparous cows was accompanied by an increase non-esterified fatty acids concentration by 1.75-2 times. The level of AST was the lowest in the serum of gestating cows several days before calving, whereas after calving, an increase was observed. It was discovered that each group had animals with AST levels above 100 U/L. There were 20 % of animals in the 5-7 pre-calving group, and 80% in the 7-10 post-calving group. The level of total bilirubin in the group of primiparous cows 2-3 PC exceeded the level BC by 3.14 times, and in the group 7-10 post-calving by 2.67 times. In the BC group, 20% of cows during their 2nd-3rd lactation were found to have ketonemia, with beta-hydroxybutyrate level 1.43 mmol/L in the serum. The highest level of ketone bodies was detected in cows from the group 2-3 PC, with 60% showing subclinical and 20% showing clinical ketosis. Similarly to primiparous cows, cows in their 2nd-3rd lactation exhibited the development of negative energy balance in the postpartum period. In the group of cows BC, AST activity exceeded 100 U/L in 20% of animals, while in the groups 2-3 PC and 7-10 PC, the number of such animals reached 60%. These changes were accompanied by hyperbilirubinemia, which was observed after calving in 80% of cows in both groups. Therefore, an increase non-esterified fatty acids levels was observed in the postpartum period in primiparous cows and cows in their 2nd-3rd lactation of the Brown Swiss breed. The results indicate the development of lipomobilization syndrome. The most pronounced signs of ketosis development were observed in primiparous cows on days 7-10 after calving, while in multiparous cows, it was detected on days 2-3. The development of negative energy balance led to signs of liver damage characteristic of lipidosis - an increase in total bilirubin levels and, to a lesser extent, AST activity. Biochemical index changes during post-calving period were observed in primiparous cow with more prominent level. However, during late dry period metabolic disorders were detected in multiparous cow in which observed ketonemia. Кетоз є одним з найбільш поширених захворювань серед поголів’я молочних корів, що завдає значних економічних збитків та потребує подальшого вивчення патогенезу. Зокрема, це стосується менш традиційних молочних порід худоби, у тому числі, швіцької. Метою роботи було дослідити біохімічні показники у різновікових корів швіцької породи у стаді з поширеним кетозом. Дослідження проведено у стаді молочних корів із рівнем кетозу понад 30 %. Для проведення досліджень проводили відбір проб крові у первісток та корів 2-3 лактації за 5-7 діб до отелення (група ВС) та через 2-3 (група 2-3 РС) 7-10 (група 7-10 РС) діб після нього. Визначення біохімічних показників сироватки крові, спрямованих на визначення рівню ліпомобілізації, кетонових тіл та функціонального стану печінки, проводили з використанням автоматичного біохімічного аналізатору. У групі первісток 2-3 РС спостерігалося наростання вмісту бета-гідроксибутирату в 1,83 рази, а кетонемія була у 40 % корів. Післяотельний період у первісток супроводжувався зростанням концентрації неестерифікованих жирних кислот в 1,75-2 рази. У сироватці крові нетелів за кілька днів до отелення рівень АСТ був найнижчим, а після отелення спостерігалося його підвищення. В кожній з груп виявлялися тварини з рівню АСТ понад 100 Од/л – в групі 5-7 ВС у 20%, а в групі 7-10 РС – у 80%. Рівень загального білірубіну у групі первісток 2-3 РС перевищував рівень до отелення в 3,14 рази, а в групі 7-10 РС у 2,67 рази. У сироватці крові корів 2-3 лактації групи 5-7 ВС виявлено 20 % тварин з кетонемією (рівень бета-гідроксибутирату 1,43 ммоль/л). Найвищий рівень кетонових тіл було встановлено у корів групи 2-3 РС, серед яких 60 % мали субклінічний, а 20 % – клінічний кетоз. Аналогічно до первісток, у корів 2-3 лактації у післяотельний період спостерігався розвиток негативного енергетичного балансу. У групі корів ВС активність АСТ у 20 % тварин перевищувала значення 100 Од/л, а в групах 2-3 РС та 7-10 РС кількість таких тварин досягала 60 %. Такі зміни супроводжувалися білірубінемією. Вона виявлялася після отелення у 80 % корів обох груп. Отже, у первісток та корів 2-3 лактації швіцької породи у післяотельний період спостерігалося підвищення рівню неестерифікованих жирних кислот, що вказує на розвиток ліпомобілізаційного синдрому. Найбільш виражені ознаки розвитку кетозу спостерігалися у первісток на 7-10 добу після отелення, тоді як у корів – на 2-3 день. Розвиток негативного енергетичного балансу призводив до ознак ураження печінки, характерних для ліпідозу – підвищення рівню загального білірубіну та, менш виражено, активності АСТ. Зміни біохімічних показників в післяотельний період були вираженішими у первісток, однак, у багатоотельних корів були виявлені метаболічні розлади з проявом кетонемії наприкінці сухостійного періоду.
Біохімічні порушення у корів швіцької породи з кетозом в перинатальний період
Єфімов Валентин Геннадійович https://orcid.org/0000-0002-4286-8567
Keywords: beta-hydroxybutyrate; бета-гідроксибутират; calving; отелення; Brown Swiss cattle; швіцька худоба; lipomobilization; ліпомобілізація; liver lipidosis; ліпідоз печінки; hyperbilirubinemia; білірубінемія; NEFA; НЕЖК